The politics of urban governance - Pierre, Jon (Palgrave Macmillan, 2011)
"This broad ranging new text analyses the emerging shape of urban politics in the twenty-first century. The author identifies 4 main "models" of urban governance--"management," "Corporatist." "Pro-Growth" and "Welfare"--and assesses their different implications for the major issues, interests and problems in the contemporary urban arena"--